Ultrastructure evaluation of Pasteurella multocida B:2 in respiratory organs of aerosolly-infected mice - Raazali, Razila (2017)
Haemorrhagic septicaemia (HS) is an acute, fatal, septicaemic disease of buffaloes and cattle caused by Pasteurella multocida B:2. Natural cases of HS occur primarily via the aerogenous route of susceptible animals. This study was conducted to determine and evaluate ultrastructure of respiratory organ with respect to aerosol inoculation of P. multocida in mice which mimics natural HS transmission. A group of 30 healthy female mice were divided into two groups, control (n=5) and treatment. The treatment groups were further divided equally into 5 groups (n=5). All treatment group were inoculated aerosolly with 10 ml of 1 X 109 cfu/mL of P. multocida for 20 minutes. The control group were euthanised at 6 h prior to inoculation, while the treatment groups were euthanised by cervical dislocation at 0, 6, 12, 18, 24 h pi. Clinical signs were observed for 24 h pi. Lungs tissue were collected for ultrastructural examination. Clinical signs of reduced activity were observed starting from 12 to 24 h pi. The ultrastructure evaluation for the treatment groups showed mild to severe degree of pathological changes in the pneumocyte and endothelial cell. Overall, inoculation of P. multocida Type B:2 via aerogenous route revealed significant (p<0.05) cellular changes on the lungs.